Profitability and Leverage as Determinants of Dividend Policy: Evidence of Turkish Financial Firms - Hariem Abdullah (Eurasian Journal of Management & Social Sciences)
The purpose of this study is to investigate the impact of profitability and leverage ratios on the determination of dividend policy for Turkish financial firms listed on Borsa Istanbul. In order to do so, secondary longitudinal data were collected for the listed financial firms from the DataStream database over the period 2008-2020. The financial crisis of 2007-2008 affected the sector undoubtedly. Thus, it is important to investigate how dividend policy behaves with debt level and level of profitability in the financial sector of developing countries after the well-known financial crisis.  The research expects that both profitability and leverage have a significant correlation with the dividend payout ratio. Consistent to the findings of the majority of the prior empirical studies, the results of this study found that both profitability and leverage are negatively associated with the dividend payout ratio.